Magnetic field effect on thermal impermanence in a nanofluid layer with low Prandtl number through porous medium - Deepak Kapil, Sudhir Kumar, Rimple Pundir (International Journal of Advanced Science and Technology, 2020)
The numerical and analytical investigation have been done in this research article on the impression of magnetic field on thermal impermanence a low Prandtl number nanofluid layer through a porous medium. By applying Perturbation method, Normal mode technique, the dispersion relation has been derived. The impressions of the different physical parameters of the system, namely Lewis number, modified diffusivity ratio, Darcy number, Prandtl number and magnetic field on the stationary deportation have been reported analytically as well as graphically. The Prandtl number and Darcy number show destabilizing impression whenever Lewis number and modified diffusivity ratio show to stabilizing impression for negative value of concentration Grashof number whereas magnetic field has a stabilizing impression for stationary deportation Keyelements: : Lewis number, magnetic field, nanofluid, Prandtl number